(untitled) (Journal of Economic Research & Business Administration, 2022)
The BRIC countries are the four largest emerging economies, accounting for a quarter of the world’s total GDP. The external debt stock of the BRIC countries (3938 billion USD) corresponds to 46.22% of the total foreign debt stock of the developing countries (8520 billion USD). The role of foreign debt in the economic development of a country is one of the most discussed and interesting topics in macroeconomics among researchers and politicians. Therefore, in this study, the relationship between foreign borrowing and economic growth in BRIC countries was examined. The data set used in the study belongs to the years 1990-2021 and panel cointegration method was used. As a result of the Westerlund (2007) panel cointegration test applied, a long-term relationship was found between foreign borrowing and economic growth variables in BRIC countries. The long-run cointegration vector was estimated with the panel FMOLS estimator. According to our results; The long-run regression coefficient between external debt and economic growth in BRIC countries is -0.1108. This means that when the external debt stock in these countries increases by 1%, economic growth decreases by 0.11%. When evaluated on the basis of countries, the relationship between foreign debt and economic growth is positive for China, while the relationship is negative for Brazil, Russia and India. Key words: BRIC, External debt, economic growth, panel data analysis